Performance of Broiler Finisher Chicks Fed Varying Levels of Maize Offal as Replacement for Whole Maize - Ekenyem, B.U.; Obih, T.K.O. (International Journal of Poultry Science, 2010)
Two hundred 4-week old Anak 1000 Strain of broliles were used in a 28-day feeding trial in a completely randomized design to evaluate the performance of finisher broiler chicken fed varying levels of maize further replicated four times. Treatments having 0, 15, 30, 45 and 60% maize offal replaced corresponding weights of whole maize in the diets. Feed and water were supplied ad libitum. Routine vaccination programme and medication typical of measured. Results who that birds on control (0%) and 30% maize offal with weight gains of 1.56 kg and 1.55 kg respectively did not differ significantly (p>0.05) but were significantly (p>0.05) heavier than those on 15, 45 and 60%. Cost of producing one kg of feed declined from N54.50 in the conrol to N44.50 at 60% inclusion level of maize offal which differed significantly (p>0.05). Feed cost/kg gain (N) was lowest for birds on T3 (30% maize offal), N 145.08 which differed significantly (p>0.05) from the other treatments.